2011
DOI: 10.1007/s10329-011-0249-3
|View full text |Cite
|
Sign up to set email alerts
|

Capuchin monkeys (Cebus apella) modify their own behaviors according to a conspecific’s emotional expressions

Abstract: Understanding conspecifics' emotional states is important for managing social interactions. We examined whether capuchin monkeys modify their own behaviors in response to a conspecific's emotional expressions. Six monkeys saw a demonstrator monkey responding emotionally to an object in a container; the subject monkeys could not see the object. The subjects reached for the container more frequently when the demonstrator showed an emotionally positive expression than when she showed an emotionally neutral or neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
0
22
1
1
Order By: Relevance
“…An experimental approach focusing on monkeys' ability or inability to recognize others' emotional states can contribute to this debate. Previous studies have shown that monkeys modify their own behavior according to conspeciWcs' emotional expressions (Miller et al 1963(Miller et al , 1966Morimoto and Fujita 2011). However, these results may be explained by emotional contagion: observers' own emotional states, and thus, their behavior might have been aVected by the model's emotional expressions (HatWeld et al 1994).…”
Section: Introductioncontrasting
confidence: 53%
See 1 more Smart Citation
“…An experimental approach focusing on monkeys' ability or inability to recognize others' emotional states can contribute to this debate. Previous studies have shown that monkeys modify their own behavior according to conspeciWcs' emotional expressions (Miller et al 1963(Miller et al , 1966Morimoto and Fujita 2011). However, these results may be explained by emotional contagion: observers' own emotional states, and thus, their behavior might have been aVected by the model's emotional expressions (HatWeld et al 1994).…”
Section: Introductioncontrasting
confidence: 53%
“…The bar shows mean choice rate and black dot shows performance of each observer monkey in Negative, Neutral, and Positive conditions. Note that only one container was opened to evoke an emotional reaction by the demonstrator As noted earlier, previous studies demonstrated that monkeys responded diVerently depending upon conspeciWcs' emotional expressions (Miller et al 1963(Miller et al , 1966Morimoto and Fujita 2011), but these eVects may be explained by emotional contagion. However, the present results show that monkeys associated speciWc objects with the emotions that they elicited in the demonstrator.…”
Section: Discussionmentioning
confidence: 91%
“…A number of species can use the emotional expressions of others to guide their own behavior (e.g., Morimoto and Fujita, 2011); however, few studies have examined whether there are sex differences in sensitivities to conspecifics’ emotional expressions. For example, when viewing a conspecific in pain, the pain-associated behaviors in the viewer (e.g., writhing) can indicate the amount of empathy.…”
Section: Evolutionary Precursors Of Empathymentioning
confidence: 99%
“…In monkeys encountering a novel object, the concurrent display of positive and negative facial expressions bias approach and avoidance behaviors, respectively [100]. Tree shrews respond differentially to the same call produced with high and low affective intensity [101].…”
Section: Sensory Modalities For Emotion Expressionmentioning
confidence: 99%